A method for preparing FCAA by electrochemical in-situ oxidation of FCA

Through the electrochemical in-situ oxidation method, the electrode and separator system are used to generate reactive oxygen species in the electrolyte, achieving efficient oxidation of FCA, solving the problems of harsh reaction conditions and insufficient selectivity of the existing chemical oxidation methods, and achieving high selectivity, high yield and high purity FCAA preparation.

CN116005179BActive Publication Date: 2025-04-01WANHUA CHEM GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310001822.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2025-04-01
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

When the existing chemical oxidation method oxidizes 2-methyl-4-acetoxy-2-butenal (FCA) to 2-methyl-4-acetoxy-2-butenal (FCAA), there are problems of harsh reaction conditions, serious post-treatment and corrosion conditions, and insufficient selectivity and yield.

Method used

Using an electrochemical in-situ oxidation method, an electrode supporting the oxygen reduction reaction is used as the cathode, an inert electrode as the anode, and a separator is provided between the cathode and the anode. A mixture of water and organic solvent added to support the electrolyte is used as the electrolyte, and oxygen is introduced to the cathode to undergo an oxygen reduction reaction, and the reactive oxygen species ROS is generated in situ to achieve indirect oxidation of FCA.

Benefits of technology

It achieves high selectivity and high yield FCA oxidation, avoids the use of added chemical oxidants, reduces raw material costs and reaction risks, and has high product purity, which is in line with the concept of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004034261150000071
    Figure BDA0004034261150000071
  • Figure HDA0004034261160000011
    Figure HDA0004034261160000011
Patent Text Reader

Abstract

The present invention provides a method for preparing 2-methyl-4-acetoxy-2-butenoic acid (FCAA) by electrochemical in-situ oxidation of 2-methyl-4-acetoxy-2-butenal (FCA), using an electrode supporting oxygen reduction reaction as a cathode, an inert electrode as an anode, and a mixture of water and an organic solvent with a supporting electrolyte added as an electrolyte solvent to form an electrochemical reaction system, wherein the oxygen undergoes an oxygen reduction reaction at the cathode, and active oxygen species are generated in situ to achieve indirect electrochemical oxidation of FCA. The method of the present invention avoids the post-treatment and corrosion problems of conventional chemical oxidation that introduces halogens by adding halogen-containing oxidants, and at the same time, the anode region is isolated by a cation exchange membrane, and ROS generated in situ in the cathode region is used to achieve indirect oxidation in the cathode region, thereby avoiding the problem of over-oxidation that may be caused by direct electrochemical oxidation of FCA by the anode, and greatly improving the selectivity of the FCAA product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical intermediate preparation, and particularly relates to a method for preparing 2-methyl-4-acetoxy-2-butenoic acid by electrochemical in-situ oxidation of 2-methyl-4-acetoxy-2-butenal. Background Art

[0002] 2-Methyl-4-acetoxy-2-butenal (FCA) is an important intermediate in the synthesis of vitamin A and is produced in large quantities during the production of vitamin A. Its oxidation product, 2-methyl-4-acetoxy-2-butenoic acid (FCAA), is an important intermediate fragment in the synthesis of vitamin A derivative industry chain, such as carotenoids (β-carotene, canthaxanthin, apo ester, etc.). Due to its extensive application in this field, the efficient oxidation of excess FCA in the vitamin A industry chain to FCAA and its application in the derivative industry chain has long been a research hotspot.

[0003] There are currently a variety of methods for oxidizing FCA to FCAA, and the advantages and disadvantages of each route are discussed in detail in the literature.

[0004] The current mainstream oxidation method is chemical oxidation. CN102863367A discloses the use of 4-acetoxy-2-methyl-2-butenal in the presence of H 2 O 2 、NaClO 2 The method of preparing 4-acetoxy-2-methyl-2-butenoic acid by oxidation reaction with an oxidant in the presence of a buffer needs to maintain a low temperature to prevent a violent reaction. After the reaction is completed, a quencher needs to be added to quench the excess oxidant to obtain the product FCAA. Not only are the raw materials used complex, but the reaction conditions are also harsh, and the post-treatment and corrosion are also serious, which does not conform to the concept of green chemistry.

[0005] Research in recent years has found that using electrochemical oxidation to replace conventional chemical oxidation can meet the requirements of high yield and high selectivity while being more environmentally friendly, low-carbon and economical. However, direct electrochemical oxidation does not have sufficient control over the oxidation capacity, which leads to over-oxidation when electrochemically oxidizing certain compounds, seriously affecting the selectivity. Based on this problem, it is still necessary to develop new processes based on electrochemical oxidation to achieve higher selectivity. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing FCAA by oxidizing FCA through in-situ electrochemical generation of ROS, which can meet the requirements of high yield and high selectivity while avoiding the inevitable disadvantages of conventional chemical oxidant oxidation.

[0007] The invention discloses a method for preparing 2-methyl-4-acetoxy-2-butenoic acid (FCAA) by electrochemical in-situ oxidation of 2-methyl-4-acetoxy-2-butenal (FCA). The method comprises the following steps: using an electrode supporting oxygen reduction reaction as a cathode, an inert electrode as an anode, a diaphragm between the cathode and the anode, and using a mixture of water and an organic solvent added with a supporting electrolyte as an electrolyte solvent to form an electrochemical reaction system. Oxygen introduced undergoes an oxygen reduction reaction at the cathode, and reactive oxygen species ROS are generated in-situ to achieve indirect oxidation of FCA to obtain FCAA.

[0008] In a specific embodiment, the cathode is a modified graphite felt carbon material gas diffusion electrode.

[0009] In a specific embodiment, the modification method of the modified graphite felt carbon material gas diffusion electrode is:

[0010] 1) Soak the graphite felt electrode in deionized water, then put it into a mixed dilute sulfuric acid / nitric acid solution, heat it to boiling, keep boiling for 30-60 minutes, take it out, wash it with deionized water until the washing liquid is not acidic, let it stand, and dry it;

[0011] 2) Connect the acid-boiled graphite felt to the electrochemical workstation and keep it at the anode potential of 1.5-3.0V vsAg / Ag + Cyclic voltammetry scanning was performed with the scanning number >500. After the cyclic voltammetry scanning was completed, the electrode was taken out to obtain a modified graphite felt carbon material gas diffusion electrode.

[0012] In a specific embodiment, the inert electrode of the anode is selected from TiO 2 / Ti electrode or platinum electrode.

[0013] In a specific embodiment, the membrane is selected from a cation exchange membrane, preferably a perfluorosulfonic acid cation exchange membrane, a SiO 2 Any of modified Nation 117 cation exchange membrane and Japanese AGC cation exchange membrane; more preferably, perfluorosulfonic acid cation exchange membrane.

[0014] In a specific embodiment, the supporting electrolyte is selected from Na 2 SO 4 , K 2 SO 4 、NaHSO 4 , KHSO 4 At least any one of the above, preferably, the concentration of the supporting electrolyte in the electrolyte solvent is 300-400 ppm.

[0015] In a specific embodiment, the organic solvent is a protic solvent, preferably any one of acetonitrile, methanol and ethanol. Preferably, the mass concentration of the acetonitrile aqueous solution is 10-30%.

[0016] In a specific embodiment, the oxygen flow rate is 0.4-1 mL / min, and the stirring rate is 100-250 rpm.

[0017] In a specific embodiment, the cathode potential is -1.0 to -1.3 V vs Ag / Ag + .

[0018] In a specific embodiment, the temperature of the electrochemical reaction is 20-40° C., and the time of the electrochemical reaction is 2-6 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) The method of the present invention does not require the addition of an external chemical oxidant. At the same time, the active oxygen species themselves have self-quenching properties, and there is no need to add a quencher, which saves the cost of raw materials. After the reaction is completed, a pure reaction system can be obtained, which greatly reduces the difficulty of separation and improves the purity of the product.

[0021] 2) The method of the present invention adopts electrochemical in-situ indirect oxidation, which avoids the introduction of halogen oxidants and reduces the three waste environmental protection problems and corrosion problems; at the same time, the reaction conditions are mild and the reaction risk is small.

[0022] 3) The in-situ electrochemical oxidation FCA method of the present invention has high selectivity, high yield and high product purity. The yield of the method can reach 97% in 2 hours, and the selectivity is greater than 99%. At the same time, the cost of raw materials is effectively reduced, and it is a very green, environmentally friendly and economical FCA oxidation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are electron microscope images of the carbon material gas diffusion electrode used as the cathode of the present invention before and after modification, wherein the left side is before modification and the right side is after modification). DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0025] The invention discloses a method for preparing 2-methyl-4-acetoxy-2-butenoic acid (FCAA) by electrochemical in-situ oxidation of 2-methyl-4-acetoxy-2-butenal (FCA). The method comprises the following steps: using an electrode supporting oxygen reduction reaction as a cathode, an inert electrode as an anode, a diaphragm between the cathode and the anode, and using a mixture of water and an organic solvent added with a supporting electrolyte as an electrolyte solvent to form an electrochemical reaction system. Oxygen introduced undergoes an oxygen reduction reaction at the cathode, and reactive oxygen species ROS are generated in-situ to achieve indirect oxidation of FCA to obtain FCAA.

[0026] The electrochemical FCA oxidation method of the present invention adopts a mixture of acetonitrile and water with added supporting electrolyte as the electrolyte solvent of the electrochemical system, and uses a carbon material gas diffusion electrode that can undergo oxygen reduction reaction by adding oxygen as the cathode, thereby achieving a high-selectivity and high-yield FCA oxidation technical effect.

[0027] The inventors speculate that the principle may be that the added oxygen undergoes an oxygen reduction cathode reaction at the cathode, O 2 Get 1e - or 2e - , generating reactive oxygen species (such as H 2 O 2 , O 2 - , O - At the same time, due to the presence of the cation exchange membrane, FCA will not be directly electrochemically oxidized at the anode, thus avoiding the problem of over-oxidation and greatly improving the selectivity.

[0028] Specifically, the method for preparing FCA by electrochemical oxidation of the present invention comprises the following steps:

[0029] 1. Preparation of cathode carbon material modified graphite felt:

[0030] 1) Soak the graphite felt electrode in deionized water at room temperature (20-30°C), then put it into a mixed dilute sulfuric acid / nitric acid solution (concentration of 5-10wt%), heat it to boiling, keep boiling for 30-60 minutes, take it out, wash it with deionized water at room temperature until the washing liquid is not acidic, let it stand, and dry it at 50-60°C and 0.01-0.03mPa for 8-12 hours;

[0031] 2) Connect the acid-boiled graphite felt to the electrochemical workstation and keep it at the anode potential of 1.5-3.0V vsAg / Ag + Cyclic voltammetry scanning was performed with a scanning number of 500-800 r. After the cyclic voltammetry scanning was completed, the electrode was taken out to obtain a modified graphite felt carbon material gas diffusion electrode, which was cut into small pieces of 1 cm*1 cm for later use.

[0032] Electron microscopy images before and after modification Figure 1 As shown in the figure, a large number of oxygen-containing functional groups can be modified on the surface of carbon fiber after acid boiling, increasing the affinity for oxygen-containing substances. A large number of cracks and rough surfaces will appear on the surface of graphite felt fiber after CV etching, which increases the effective surface area of ​​the electrode, makes it more fully in contact with dissolved oxygen, and has a better oxygen reduction reaction (ORR) effect.

[0033] 2. Configuration of electrolyte solvent and addition of raw materials:

[0034] Add a certain amount of acetonitrile to deionized water to prepare a 10-30% acetonitrile aqueous solution (acetonitrile serves as a dual role of dissolving organic matter and supporting electrolyte), and then add a certain amount of supporting electrolyte (Na 2 SO 4 , K 2 SO 4 、NaHSO 4 , KHSO 4 After the configuration is completed, the electrolyte solvent is added to the electrolytic cell, and the raw material FCA is added to the cathode area.

[0035] 3. Pretreatment before experiment:

[0036] Assemble the electrode system (cathode, anode, reference electrode Ag / Ag + ), first start stirring, stirring rate is 100-250rpm / min, then introduce oxygen near the cathode, oxygen flow rate is 0.4-1mL / min, after oxygen is introduced for 10-20min, wait until it is saturated, maintain oxygen flow rate, at this flow rate far exceeds the amount of oxygen required for FCA oxidation, control flow rate is to make the oxygen near the cathode in the system always in a saturated state. Apply cathode potential of -1.0~-1.3V vs Ag / Ag + The reaction temperature is 20-40°C and the reaction time is 2-6 hours.

[0037] The electrode for the oxygen reduction reaction as the cathode is not particularly limited in form, but is preferably a gas diffusion electrode, and various carbon electrode materials can be used. At the same time, it can be modified to further increase the effective area of ​​the electrode and the affinity for oxygen-containing substances.

[0038] From the perspective of enhancing the solubility of the raw material FCA and supporting electrolysis, it is more preferred to add an organic solvent and a supporting electrolyte to water. For example, there are organic solvents such as methanol, ethanol, and acetonitrile. The selected organic solvent must meet the following two conditions: 1) miscible with water; 2) not affecting the conductivity of the system. Acetonitrile is preferably used as the organic solvent of the present invention. When an organic solvent is added, the mass proportion of the organic solvent is about 10-30%, for example 10%, 15%, 20%, 25%, 30%, etc., preferably in the range of 15-25%.

[0039] The supporting electrolyte is Na 2 SO 4 , K 2 SO 4 、NaHSO 4 , KHSO 4 One or more of the above, the concentration is 300-400ppm, for example 300ppm, 310ppm, 320ppm, 330ppm, 340ppm, 350ppm, 360ppm, 370ppm, 380ppm, 390ppm, 400ppm, etc., preferably Na 2 SO 4 .

[0040] There is no particular limitation on the anode used in the FCA oxidation reaction of the present invention, and any inert electrode may be used, for example, a platinum electrode, a titanium alloy electrode or other commonly used inert electrode.

[0041] The membrane used in the FCA oxidation reaction of the present invention is a cation exchange membrane, such as a perfluorosulfonic acid cation exchange membrane, a SiO 2 Any of modified Nation 117 cation exchange membrane and Japan AGC cation exchange membrane; more preferably, perfluorosulfonic acid cation exchange membrane.

[0042] In the electrochemical oxidation reaction of FCA of the present invention, the electrochemical reaction conditions are as follows: the cathode potential is -1.0 to -1.3 V vs Ag / Ag + , e.g. -1.0V, -1.1V, -1.2V, -1.3V vs Ag / Ag + The temperature of the electrochemical reaction is 20-40°C, such as 20°C, 25°C, 30°C, 35°C, 40°C, etc. The time of the electrochemical reaction is 2-6 hours, such as 2h, 3h, 4h, 5h, 6h, etc. It is further preferred to use a cathode potential of -1.1 to -1.3V vs Ag / Ag + , the reaction temperature is 25-35°C, and the electrochemical reaction time is in the range of 2 to 3 hours.

[0043] Among them, the cathode potential is -1.0~-1.3V vs Ag / Ag + , is the potential displayed relative to the silver / silver ion reference electrode. In the present invention, for example, according to the optimal experimental conditions, the current in the reaction is 300-500mA, and the cathode electrode area of ​​the present invention is 1cm*1cm. At this time, the current density is 300-500mA / cm 2 .

[0044] In the present invention, unless otherwise specified, percentages refer to mass percentages and temperatures are in degrees Celsius (°C).

[0045] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0046] The raw material FCA used is produced by the VA device and is an intermediate in the VA production process. It can also be purchased from Zhejiang Medicine. The chemical structural formulas of the FCA raw material and FCAA product used in the following examples are as follows:

[0047]

[0048] The FCA conversion, selectivity and purity in the examples are determined as follows:

[0049] Degradation rate evaluation was performed using a gas chromatograph: Agilent 7820A gas chromatograph, DB-5 capillary column, injection volume: 0.2 μl. The test method is as follows:

[0050] Inlet temperature: 240°C, initial column temperature 60°C, maintained for 2 min, then increased to 200°C at a rate of 15°C / min, maintained for 10 min, and the total running time was 21.33 min.

[0051] First, a series of FCA and FCAA standard substances with standard concentrations were prepared to establish a standard curve of spectrum peak area and concentration through gas chromatography. Then, the substances after electrochemical reaction were used for testing, and the concentrations of reactants and products were obtained by substituting into the standard curve, and then the conversion rate and selectivity of the reaction were calculated.

[0052] Preparation Example 1

[0053] The modification method of the modified graphite felt carbon material gas diffusion electrode is:

[0054] 1) Soak the graphite felt electrode in deionized water at 25°C, then put it into a mixed dilute sulfuric acid / nitric acid solution (concentration of 5wt%), heat it to boiling, keep boiling for 30min, take it out, wash it with deionized water at 20°C until the washing solution is not acidic, let it stand, and dry it at 50°C, 0.01mPa for 8h;

[0055] 2) Connect the acid-boiled graphite felt to the electrochemical workstation and keep it at the anode potential of 1.5V vs Ag / Ag + Cyclic voltammetry scanning was performed with a scanning number of 500. After the cyclic voltammetry scanning was completed, the electrode was taken out to obtain a modified graphite felt carbon material gas diffusion electrode, which was cut into small pieces of 1 cm*1 cm for later use.

[0056] Preparation Example 2

[0057] 1) Soak the graphite felt electrode in deionized water at 25°C, then put it into a mixed dilute sulfuric acid / nitric acid solution (concentration of 10wt%), heat it to boiling, keep boiling for 60min, take it out, wash it with deionized water at 30°C until the washing solution is not acidic, let it stand, and dry it at 60°C, 0.03mPa for 12h;

[0058] 2) Connect the acid-boiled graphite felt to the electrochemical workstation and keep it at the anode potential of 3.0 V vs Ag / Ag + Cyclic voltammetry scanning was performed with a scanning number of 800. After the cyclic voltammetry scanning was completed, the electrode was taken out to obtain a modified graphite felt carbon material gas diffusion electrode, which was cut into small pieces of 1 cm*1 cm for later use.

[0059] Example 1

[0060] Weigh 101.8 g of acetonitrile solution and add it to 402.9 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.15 g of solid was added to the above solution at a concentration of about 300 ppm.

[0061] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.6 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 97.8% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0062] Example 2

[0063] Weigh 50.2 g of acetonitrile solution and add it to 451.1 g of deionized water to prepare a 10% acetonitrile / water solution; weigh Na 2 SO4 0.15 g of solid was added to the above solution at a concentration of about 300 ppm.

[0064] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.4 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 76.2% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0065] Example 3

[0066] Weigh 150.6 g of acetonitrile solution and add it to 349.6 g of deionized water to prepare a 30% acetonitrile / water solution; weigh NaHSO 4 0.15 g of solid was added to the above solution at a concentration of about 300 ppm.

[0067] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.4 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 88.7% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0068] Example 4

[0069] Weigh 100.6 g of acetonitrile solution and add it to 403.7 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0070] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.5 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 98.1% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0071] Example 5

[0072] Weigh 100.4 g of methanol solution and add it to 401.3 g of deionized water to prepare a 20% acetonitrile / water solution; weigh KHSO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0073] In the SiO 2 In the diaphragm electrolyzer of the modified Nation 117 cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, and the TiO 2 / Ti electrode as anode, Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.4 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 97.6% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0074] Example 6

[0075] Weigh 101.4 g of ethanol solution and add it to 398.9 g of deionized water to prepare a 20% acetonitrile / water solution; weigh K 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0076] In a diaphragm electrolyzer equipped with a Japanese AGC cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.6 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.4 mL, the stirring speed was 250 rpm, and the system was ventilated for 40 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 71.5% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0077] Example 7

[0078] Weigh 102.8 g of acetonitrile solution and add it to 401.2 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0079] In a diaphragm electrolyzer equipped with a Japanese AGC cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.3 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 1.0 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 98.0% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0080] Example 8

[0081] Weigh 101.5 g of acetonitrile solution and add it to 401.4 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0082] In the SiO 2 In the diaphragm electrolyzer of the modified Nation 117 cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.6 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 200 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 91.2% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0083] Example 9

[0084] Weigh 102.1 g of acetonitrile solution and add it to 401.9 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0085] In a diaphragm electrolyzer equipped with a Japanese AGC cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.7 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.0 V for 2 hours. The FCA conversion rate was 62.1% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0086] Example 10

[0087] Weigh 101.4 g of acetonitrile solution and add it to 402.4 g of deionized water to prepare a 20% acetonitrile / water solution; weigh NaHSO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0088] In the SiO 2 In the diaphragm electrolyzer of the modified Nation 117 cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.6 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.3 V for 2 hours. The FCA conversion rate was 98.1% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0089] Embodiment 11

[0090] Weigh 102.5 g of acetonitrile solution and add it to 401.9 g of deionized water to prepare a 20% acetonitrile / water solution; weigh KHSO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0091] In the SiO 2 In the diaphragm electrolyzer of the modified Nation 117 cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.7 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 20°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 94.7% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0092] Example 12

[0093] Weigh 99.89 g of acetonitrile solution and add it to 401.0 g of deionized water to prepare a 20% acetonitrile / water solution; weigh K 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0094] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.5 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 40°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 97.9% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0095] Embodiment 13

[0096] Weigh 100.1 g of methanol solution and add it to 400.7 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0097] In a diaphragm electrolyzer equipped with a Japanese AGC cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the above-configured solution was added; 25.4 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 6 hours. The FCA conversion rate was 98.3% and the selectivity was >99% when analyzed by gas chromatography (GC).

[0098] Embodiment 14

[0099] Weigh 100.6 g of methanol solution and add it to 403.7 g of deionized water to prepare a 20% acetonitrile / water solution; weigh K 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0100] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, the modified graphite felt electrode prepared in Preparation Example 2 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode is used as the reference electrode to establish a three-electrode system, and the above-configured solution is added; 25.5 g of FCA is weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode is adjusted to 0.8 mL, the stirring speed is 250 rpm, and the system is ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere is continuously introduced at 25°C, and constant potential electrolysis is performed at a cathode potential of -1.2 V for 2 hours. Using gas chromatography (GC) for analysis, the FCA conversion rate is 98.0%, and the selectivity is >99%.

[0101] Comparative Example 1

[0102] Weigh 100.6 g of acetonitrile solution and add it to 403.7 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0103] In a diaphragm electrolyzer equipped with a perfluorosulfonic acid cation exchange membrane, an unmodified graphite felt electrode was used as the cathode, a platinum sheet electrode was used as the anode, and an Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, and the solution configured above was added; 25.6 g of FCA was weighed and added to the cathode area of ​​the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 43.9% and the selectivity was 76.2% when analyzed by gas chromatography (GC).

[0104] Comparative Example 2

[0105] Weigh 100.6 g of acetonitrile solution and add it to 403.7 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0106] In the diaphragm electrolyzer, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag +The electrode was used as the reference electrode to establish a three-electrode system, without adding a cation exchange membrane, and the above-configured solution was added; 25.6 g of FCA was weighed and added to the electrolytic cell to completely dissolve it; the oxygen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the system with oxygen; the oxygen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was 99.5% and the selectivity was 85.2% when analyzed by gas chromatography (GC).

[0107] Comparative Example 3

[0108] Weigh 100.6 g of acetonitrile solution and add it to 403.7 g of deionized water to prepare a 20% acetonitrile / water solution; weigh Na 2 SO 4 0.21 g of solid was added to the above solution at a concentration of about 400 ppm.

[0109] In the diaphragm electrolyzer, the modified graphite felt electrode prepared in Preparation Example 1 was used as the cathode, the platinum sheet electrode was used as the anode, and the Ag / Ag + The electrode was used as the reference electrode to establish a three-electrode system, a perfluorosulfonic acid cation exchange membrane was added, and the above-configured solution was added; 25.6 g of FCA was weighed and added to the electrolytic cell to completely dissolve it; the nitrogen flow rate near the cathode was adjusted to 0.8 mL, the stirring speed was 250 rpm, and the system was ventilated for 20 minutes to fully saturate the nitrogen in the system; the nitrogen atmosphere was continuously introduced at 25°C, and constant potential electrolysis was performed at a cathode potential of -1.2 V for 2 hours. The FCA conversion rate was <1% and the selectivity was <1% when analyzed by gas chromatography (GC).

[0110] Comparative Example 4

[0111] According to the literature method (Pi Shiqing, Jiang Hongying, Zhai Dewei, et al. Synthesis of β-apo-8'-carotene ethyl ester [J]. Journal of Chemical Engineering of Colleges and Universities, 2014, 28(6):5.), FCA was oxidized by chemical oxidation:

[0112] C5 aldehyde and methanol were added to a 3L jacketed reactor, cooled to 0°C, and 1.1 eq of H 2 O 2 Then add 2eq of sodium dihydrogen phosphate solution as a buffer, keep stirring at 0°C, stirring at a rate of 250 rpm, and slowly add another oxidant NaClO 2 , add dropwise for 2.5h, react for 3h, add sodium sulfite for quenching after the reaction is completed, and then adjust the pH to strong acidity to condense FCAA from the aqueous phase, use ethyl acetate for 3-5 times of extraction and back extraction to obtain the product FCAA, and the tested FCA conversion rate is 96.5% and the selectivity is 98.2%.

[0113] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing 2-methyl-4-acetoxy-2-butenoic acid FCAA by electrochemical in-situ oxidation of 2-methyl-4-acetoxy-2-butenal FCA, characterized in that: An electrode supporting oxygen reduction reaction is used as a cathode, an inert electrode is used as an anode, a diaphragm is provided between the cathode and the anode, a mixture of water and an organic solvent with a supporting electrolyte added is used as an electrolyte solvent to form an electrochemical reaction system, oxygen introduced undergoes an oxygen reduction reaction at the cathode, and active oxygen species ROS are generated in situ to achieve indirect oxidation of 2-methyl-4-acetoxy-2-butenal FCA to obtain 2-methyl-4-acetoxy-2-butenoic acid FCAA; The cathode is a modified graphite felt carbon material gas diffusion electrode; The membrane is selected from cation exchange membranes.

2. The method according to claim 1, characterized in that The modification method of the modified graphite felt carbon material gas diffusion electrode is: 1) Soak the graphite felt electrode in deionized water, then put it into a mixed dilute sulfuric acid / nitric acid solution, heat it to boiling, keep boiling for 30-60 minutes, take it out, wash it with deionized water until the washing liquid is not acidic, let it stand, and dry it; 2) Connect the acid-boiled graphite felt to the electrochemical workstation and keep it at the anode potential of 1.5-3.0V vs Ag / Ag + Cyclic voltammetry scanning was performed with the scanning number >500. After the cyclic voltammetry scanning was completed, the electrode was taken out to obtain a modified graphite felt carbon material gas diffusion electrode.

3. The method according to claim 1, characterized in that The inert electrode of the anode is selected from a TiO2 / Ti electrode or a platinum sheet electrode.

4. The method according to claim 1, characterized in that The membrane is selected from any one of perfluorosulfonic acid cation exchange membrane, SiO2 modified Nation 117 cation exchange membrane, and Japanese AGC cation exchange membrane.

5. The method according to claim 4, characterized in that The membrane is a perfluorosulfonic acid cation exchange membrane.

6. The method according to claim 1, characterized in that The supporting electrolyte is selected from at least any one of Na2SO4, K2SO4, NaHSO4, and KHSO4.

7. The method according to claim 6, characterized in that The concentration of the supporting electrolyte in the electrolyte solvent is 300-400 ppm.

8. The method according to claim 1, characterized in that The organic solvent is a protic solvent.

9. The method according to claim 8, characterized in that The organic solvent is any one of acetonitrile, methanol and ethanol.

10. The method according to claim 9, characterized in that The mass concentration of the acetonitrile aqueous solution is 10-30%.

11. The method according to any one of claims 1 to 10, characterized in that: The oxygen flow rate is 0.4-1 mL / min, and the stirring rate is 100-250 rpm.

12. The method according to claim 11, characterized in that Cathode potential is -1.0~-1.3V vs Ag / Ag + .

13. The method according to claim 12, characterized in that The temperature of the electrochemical reaction is 20-40° C., and the time of the electrochemical reaction is 2-6 hours.

Citation Information

Patent Citations

  • Method for synthesizing beta-apo-8'-malonic acid alkyl ester

    CN102863367A

  • Preparation and application of GO / PEDOT:PSS modified graphite felt electrode applied to heterogeneous Electro-Fenton system

    CN105905985A

  • Method for electrochemically depolymerizing lignin

    CN112831799A